RELEVANSI METODE COST PLUS PRICING UNTUK MENENTUKAN HARGA POKOK PRODUKSI PADA KONVEKSI - Fania Putri, Regita; Soebijono, Tony; Erstiawan, Martinus Sony; Arifin, Mochammad (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
This research aims to produce a standard cost of production calculation and to calculate the selling price using the cost plus pricing method. The research method is carried out directly in the field by means of observation and interviews, with secondary data sources including price data for types of fabrics, customer order data, sales data, and monthly turnover data in 2021. The data is processed and analyzed using the cost of production methods and selling price using the cost plus pricing method. The results and conclusions of this study are the cost of production calculated by the company is more than the cost of production calculated by the standard method. Likewise, with the determination of the selling price, the price set by the company is higher than the selling price calculated using the cost plus pricing method, if this continues it will cause customers to switch to similar companies that offer lower prices with relatively the same product quality.